Metal-organic framework as nanocarriers for agricultural applications: a review - Basak, Sanchari; Bhattacharyya, Puja; Pudake, Ramesh Namdeo; Lokhande, P. E.; Rednam, Udayabhaskar; Chakrabarti, Sandip (Frontiers in Nanotechnology, 2024)
Agrochemicals are substances used to promote plant growth and eradicate pests; they are essential to meeting the world food demand both qualitatively and quantitatively.Unfortunately, their extensive usage has resulted in certain significant problems i.e., soil contamination, bioaccumulation, and the development of pest resistance. Consequently, there is a need for a reduced and more regulated usage of agrochemicals. The development of sustainable nanomaterials is encouraged by agricultural nanotechnology to minimize the usage of conventional fertilizers, herbicides, and pesticides. Metal-organic Framework (MOF)s are porous materials made of functional organic ligands and metal nodes or clusters connected by covalent bonds. Researchers are becoming increasingly interested in using MOF in a variety of sectors. The features of engineered MOFs have the potential to be an optimal strategy for producing impressively unique results in agricultural research. They also have advantages in terms of biocompatibility and biodegradability, which can be leveraged to boost the efficiency of traditional pesticide administration. Controlled release of agrochemicals offers an innovative solution to decrease the nutrient uptake rates and contamination of the environment. The application of metal-organic framework nanoparticles as nanocarriers to modify the loading and release properties of agrochemicals is particularly highlighted in this review.